Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find the derivative [tex]\(\frac{dy}{dx}\)[/tex] of the function [tex]\(y = 3 \cos x \cot x\)[/tex], we will use the product rule and some trigonometric identities.
Given:
[tex]\[ y = 3 \cos x \cot x \][/tex]
Let's denote:
[tex]\[ u = 3 \cos x \][/tex]
[tex]\[ v = \cot x \][/tex]
Then [tex]\( y \)[/tex] can be rewritten as:
[tex]\[ y = u \cdot v \][/tex]
The product rule states that:
[tex]\[ \frac{d (u \cdot v)}{dx} = \frac{du}{dx} \cdot v + u \cdot \frac{dv}{dx} \][/tex]
First, we find [tex]\(\frac{du}{dx}\)[/tex]:
[tex]\[ u = 3 \cos x \][/tex]
[tex]\[ \frac{du}{dx} = 3 \cdot \frac{d (\cos x)}{dx} = 3 (-\sin x) = -3 \sin x \][/tex]
Next, we find [tex]\(\frac{dv}{dx}\)[/tex]:
[tex]\[ v = \cot x = \frac{\cos x}{\sin x} \][/tex]
Using the quotient rule:
[tex]\[ \frac{dv}{dx} = \frac{\sin x \cdot (-\sin x) - \cos x \cdot \cos x}{(\sin x)^2} \][/tex]
[tex]\[ \frac{dv}{dx} = \frac{-\sin^2 x - \cos^2 x}{\sin^2 x} = \frac{-(\sin^2 x + \cos^2 x)}{\sin^2 x} \][/tex]
Using the Pythagorean identity [tex]\(\sin^2 x + \cos^2 x = 1\)[/tex]:
[tex]\[ \frac{dv}{dx} = \frac{-1}{\sin^2 x} = -\csc^2 x \][/tex]
Now using the product rule:
[tex]\[ \frac{dy}{dx} = \frac{du}{dx} \cdot v + u \cdot \frac{dv}{dx} \][/tex]
Substituting the values of [tex]\(\frac{du}{dx}\)[/tex], [tex]\(u\)[/tex], [tex]\(\frac{dv}{dx}\)[/tex], and [tex]\(v\)[/tex]:
[tex]\[ \frac{dy}{dx} = (-3 \sin x) \cdot \cot x + (3 \cos x) \cdot (-\csc^2 x) \][/tex]
We know that [tex]\(\cot x = \frac{\cos x}{\sin x}\)[/tex] and [tex]\(\csc x = \frac{1}{\sin x}\)[/tex], so [tex]\(\csc^2 x = \frac{1}{\sin^2 x}\)[/tex].
Therefore:
[tex]\[ \frac{dy}{dx} = -3 \sin x \cdot \frac{\cos x}{\sin x} + 3 \cos x \cdot \left( -\frac{1}{\sin^2 x} \right) \][/tex]
Simplifying:
[tex]\[ \frac{dy}{dx} = -3 \cos x - 3 \cos x \cdot (\csc^2 x) \][/tex]
Putting it all together:
[tex]\[ \frac{dy}{dx} = -3 \cos x - 3 \cos x \cdot \left( \frac{1}{\sin^2 x} \right) \][/tex]
This can be further simplified as:
[tex]\[ \frac{dy}{dx} = 3 (-\cot^2 x - 1) \cos x - 3 \sin x \cot x \][/tex]
Therefore, the final form of the derivative is:
[tex]\[ 3 (-\cot^2 x - 1) \cos x - 3 \sin x \cot x \][/tex]
Given:
[tex]\[ y = 3 \cos x \cot x \][/tex]
Let's denote:
[tex]\[ u = 3 \cos x \][/tex]
[tex]\[ v = \cot x \][/tex]
Then [tex]\( y \)[/tex] can be rewritten as:
[tex]\[ y = u \cdot v \][/tex]
The product rule states that:
[tex]\[ \frac{d (u \cdot v)}{dx} = \frac{du}{dx} \cdot v + u \cdot \frac{dv}{dx} \][/tex]
First, we find [tex]\(\frac{du}{dx}\)[/tex]:
[tex]\[ u = 3 \cos x \][/tex]
[tex]\[ \frac{du}{dx} = 3 \cdot \frac{d (\cos x)}{dx} = 3 (-\sin x) = -3 \sin x \][/tex]
Next, we find [tex]\(\frac{dv}{dx}\)[/tex]:
[tex]\[ v = \cot x = \frac{\cos x}{\sin x} \][/tex]
Using the quotient rule:
[tex]\[ \frac{dv}{dx} = \frac{\sin x \cdot (-\sin x) - \cos x \cdot \cos x}{(\sin x)^2} \][/tex]
[tex]\[ \frac{dv}{dx} = \frac{-\sin^2 x - \cos^2 x}{\sin^2 x} = \frac{-(\sin^2 x + \cos^2 x)}{\sin^2 x} \][/tex]
Using the Pythagorean identity [tex]\(\sin^2 x + \cos^2 x = 1\)[/tex]:
[tex]\[ \frac{dv}{dx} = \frac{-1}{\sin^2 x} = -\csc^2 x \][/tex]
Now using the product rule:
[tex]\[ \frac{dy}{dx} = \frac{du}{dx} \cdot v + u \cdot \frac{dv}{dx} \][/tex]
Substituting the values of [tex]\(\frac{du}{dx}\)[/tex], [tex]\(u\)[/tex], [tex]\(\frac{dv}{dx}\)[/tex], and [tex]\(v\)[/tex]:
[tex]\[ \frac{dy}{dx} = (-3 \sin x) \cdot \cot x + (3 \cos x) \cdot (-\csc^2 x) \][/tex]
We know that [tex]\(\cot x = \frac{\cos x}{\sin x}\)[/tex] and [tex]\(\csc x = \frac{1}{\sin x}\)[/tex], so [tex]\(\csc^2 x = \frac{1}{\sin^2 x}\)[/tex].
Therefore:
[tex]\[ \frac{dy}{dx} = -3 \sin x \cdot \frac{\cos x}{\sin x} + 3 \cos x \cdot \left( -\frac{1}{\sin^2 x} \right) \][/tex]
Simplifying:
[tex]\[ \frac{dy}{dx} = -3 \cos x - 3 \cos x \cdot (\csc^2 x) \][/tex]
Putting it all together:
[tex]\[ \frac{dy}{dx} = -3 \cos x - 3 \cos x \cdot \left( \frac{1}{\sin^2 x} \right) \][/tex]
This can be further simplified as:
[tex]\[ \frac{dy}{dx} = 3 (-\cot^2 x - 1) \cos x - 3 \sin x \cot x \][/tex]
Therefore, the final form of the derivative is:
[tex]\[ 3 (-\cot^2 x - 1) \cos x - 3 \sin x \cot x \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.